(3EKHGJ GdYbO GdEOGQj GdEdcJQhfj (B/ s - (3eMeO MSjf YHOGdYdje MSf s; (3eMeO eMeO HOQGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JSYj gPg GdOQGSI dhVY EWGQ YGe (B"(3dEKHGJ GdYbO GdEOGQj GdEdcJQhfj(B" (3ef NdGd JgjFI Odjd cJGHj EdcJQhfj jMXi HMLjI cGedI aj GdEKHGJ Ydi bOe GdeSGhGI eY GdOdjd GdcJGHj GdhQbj(B: (3ceG Cf gPg GdOQGSI JbOe JMdjdkG dfUhU GdeYGedGJ GdEdcJQhfjI aj bhGfjf GdCee GdeJMOI(B: (3hGdEJMGO GdChQhHj(B: (3haQfSG(B: (3hHYV GdJTQjYGJ GdYQHjI ef CLd OYhI GdeTQY GdeUQj dehGcHI GdJWhQ hUjGZI bhGYO bGfhfjI LOjOI ddYbhO GdEOGQjI JSGjQ GdOhd GdeJbOeI aj gPG GdeLGd (B. (3h JQJjHG Ydi eG JbOe (B: (3h ef CLd JMbjb CgOGa gPG GdHMK GbJVJ GdMGLI Edi JbSjeg Edi HGHjf jSHbgG aUd JegjOj fJYQa ef NdGdg Ydi eaghe GdYbO GdEOGQi GdEdcJQhfi h EKHGJg HhLg YGe h jJfGhd GdHGH GdChd hSGFd EKHGJ GdYbO GdEOGQj GdEdcJQhfj h Sha jJYQV GdaUd GdChd ddcJGHI GdEdcJQhfjI(B. (3CeG GdaUd GdKGfi aSha jJfGhd GdJhbjY GdEdcJQhfj(B: (3h geG YfUQG GdOdjd GdcJGHi GdcGed(B. (3CeG GdHGH GdKGfj GdPi jYGdL GdJUOjb GdEdcJQhfj Ydj GdYbO GdEOGQj(B: (3aSha jJfGhd GdaUd GdChd efg debOe NOeGJ GdJUOjb GdEdcJQhfj(B: (3CeG GdaUd GdKGfj jJfGhd TgGOGJ GdJUOjb GdEdcJQhfj s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2016s
(3HHdjhLQGajG(B: (3UaMGJ (B249-262s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdYbO GdEOGQj GdEdcJQhfj s; (3GdJhbjY GdGdcJQhfjs; (3GGdcJGHI GdGdcJQhfjIs; (3GdJUOjb GdGdcJQhfjs; (3GdMaX GdGdcJQhfjs; (3TgGOI GdJUOjb GdGdcJQhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes